PEMETAAN DAN STRATEGI PEMANFAATAN TEKNOLOGI PADA INDUSTRI OLAHAN RUMPUT LAUT INDONESIA YANG BERKELANJUTAN - Sawarni Hasibuan (Universitas Mercu Buana, 2015)
Abstract. The fisheries industrialization program tries to place thedownstreaming of seaweed as one of the strategies to increase the added value ofthe seaweed commodity. However, the competitiveness of the national seaweedindustry is also relatively low compared to foreign industry. One of the problemsof the competitiveness of the processed seaweed industry is because the extent ofthe use of technology in the processed seaweed industry has not been identified.The purpose of this research is to map the use of technology in the processedseaweed industry in downstreaming a competitive and sustainable Indonesianseaweed industry. The mapping of the existing condition of technologyutilization refers to five indicators, namely production aspect, cost aspect, HRaspect, energy aspect, and environmental aspect. The development strategy of theseaweed downstream industry is developed by using the SWOT method. Therecommended technology standard analysis is based on the benchmark method.Results of the analysis shows that the dominant type of technology used is the„semi-mechanical technolgy‟ which mostly comes from Europe/America followedby Japan, local, and China. In order to increase the competitiveness andsustainability of the Indonesian processed seaweed industry, improvements in thefields of artificial drying, high value added (downstream) technology andtechnology for food safety is required. Several action plans required among othersare: the solar system dryer in the upstream industry, the implementation of qualityand food safety management system in the production chain, identification andinvestment of high value products in the seaweed downstream industry.Keywords: seaweed, technology assessment, SWOT, upstream and downstreamindustry